PENGARUH FINANCIAL EXPERTISE SEBAGAI DIREKTUR UTAMA TERHADAP AGRESIVITAS PAJAK DENGAN VARIABEL MODERASI TATA KELOLA - Muchammad Cholid Muttaqin; Nur Aisyah Kustiani (Polytechnic of State Finance STAN, 2022)
This study examines the effect of financial expertise as a president director on tax aggressiveness. We used financial and non-financial data of companies listed in the Indonesia Stock Exchange from 2014 to 2017. The results showed that companies led by financial expetise associated with more aggressive tax practices than other companies. From this result, we indicate that financial expertise can consider cost and benefit from tax avoidance practice. Furthermore, this study examines the effect of corporate governance on the relationship between financial expertise as a president director and tax aggressiveness. Corporate governance is measured by the proportion of independent commissioners (internal monitoring mechanism) and the proportion of institutional ownership (external monitoring mechanism). The regression results indicate the proportion of independent commissioners in both low and high conditions can’t affect the relationship between financial expertise as a president director and tax aggressiveness, while the proportion of institutional ownership also shows the same results.